1999
DOI: 10.1136/jnnp.67.5.646
|View full text |Cite
|
Sign up to set email alerts
|

Re-emergent tremor of Parkinson's disease

Abstract: (J Neurol Neurosurg Psychiatry 1999;67:646-650)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
204
3
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(220 citation statements)
references
References 28 publications
12
204
3
1
Order By: Relevance
“…Ten of those fourteen had an additional postural and/or action tremor at a similar frequency range as the ipsilateral rest tremor (bilateral, n = 8; unilateral right, n = 2; UPDRS item 21 on, median 1.5, range 0-3), which lessened transiently during action and re-emerged during posture after a delay of some seconds corresponding to postural and action tremor related to PD [37]. Postural and/or action tremor was milder and less persistent than rest tremor in all patients and none had an isolated postural and/or action tremor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten of those fourteen had an additional postural and/or action tremor at a similar frequency range as the ipsilateral rest tremor (bilateral, n = 8; unilateral right, n = 2; UPDRS item 21 on, median 1.5, range 0-3), which lessened transiently during action and re-emerged during posture after a delay of some seconds corresponding to postural and action tremor related to PD [37]. Postural and/or action tremor was milder and less persistent than rest tremor in all patients and none had an isolated postural and/or action tremor.…”
Section: Resultsmentioning
confidence: 99%
“…Essential tremor which could be a confounding factor, even though a recent VBM study had failed to detect cerebellar changes in essential tremor [14], was clinically excluded. Postural and action tremor related to PD differs from essential tremor and is considered a continuation of rest tremor during action and posture presumably originating from the same tremor generator [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although RET was first described almost 20 years ago [1], few studies have investigated the clinical features of RET.In 1999, Jankovic et al, first described RET in a small sample of patients affected by Parkinson's Disease (PD). The authors observed that PD patients with rest tremor may show a postural tremor starting after a variable delay while maintaining the upper limbs outstretched [1].…”
mentioning
confidence: 99%
“…In the second study [5] instead, only PD patients who were on their usual therapeutic regimen were studied, which means any effect of pharmacological treatment on RET was not evaluated. In this regard, unpublished investigations from our group on the presence of RET in PD patients who were evaluated both off and on treatment showed that RET was more frequent when patients were evaluated off treatment.In PD, RET usually involves the upper limbs [1,[4][5][6] and is bilateral in 50% of cases [5]. Recent clinical reports have described patients with PD with RET even in the jaw [7] and tongue [8,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation